"People make the city," executive summary : joint urban operations observations and insights from Afghanistan and Iraq - Glenn, Russell W.; Paul, Christopher, 1971-; Helmus, Todd C.; Steinberg, Paul, 1953-; International Security and Defense Policy Center; National Defense Research Institute (U.S.); Rand Corporation; United States. Joint Forces Command (Santa Monica, CA : RAND, 2007)
Today's strategic environment implies an obligation to preserve innocent life when possible and to rebuild that which war destroys. Urban areas are the keys to nations; people make nations just as, as Thucydides wrote, men make cities. This study aimed to reveal tools that will better enable military and civilian alike to meet national policy objectives by more effectively conducting urban combat and restoration. To do so, the study draws heavily on written material and interviews pertaining to Operations Enduring and Iraqi Freedom. Written information used includes thousands of pages of hard-copy and electronic material, much of it from military personnel still serving in theater at the time of its writing. Interviews include those with members of the American, British, and Australian armed forces and civilians working to reconstruct Iraq. The military personnel represent all of the services and both regular and special operations organizations. The time frame for the study corresponds to two collection phases. Phase I was conducted from October 2003 to April 2004, while Phase II was conducted during three months, from July 2004 to September 2004. The results of a third phase of the study are published separately.
Introduction -- Three overarching synthesis observations -- Observations and Insights: Understand -- Observations and insights: Shape -- Observations and insights: Engage -- Observations and insights: Consolidate -- Observations and insights: Transition -- Tactical observations and insights: selected offerings --The street ahead: how the past should influence preparations for the future.
"RAND National Defense Research Institute."
"This research was conducted within the International Security and Defense Policy Center of the RAND National Defense Research Institute"--Pg. IV.
Includes bibliographical references (p. 61-62).
Also available on the internet via WWW in PDF format.
Keywords: Street fighting (Military science); Unified operations (Military science) -- Planning; Urban warfare -- United States; United States -- Armed Forces -- Iraq